PENGEMBANGAN UMKM MELALUI PENYULUHAN PENCATATAN KEUANGAN USAHA DAN PERLINDUNGAN HUKUM TERHADAP KONSUMEN TRANSAKSI ONLINE DI DESA BATU KUDA - Ina Khodijah; Muhammad Ridwan; Dandi Mulya Permana; Dian Amelia; Popon Ruslinda; Lisa Izatul Rizqiyah (Gapenas Publisher, 2023)
The development of Micro, Small and Medium Enterprises (MSMEs) in Batu Kuda Village is carried out through business financial records and legal protection for consumers of online transactions. This service aims to improve financial management skills and understanding of consumer law for MSME actors in Batu Kuda Village. The method used is counseling. The results of the service show that MSME actors are able to understand good and correct financial records and also understand consumer rights and obligations in online transactions. This increase in skills and understanding is expected to improve the quality of MSME products and services and provide better legal protection for consumers